Effective theory for neutral resonances and a statistical dissection of the ATLAS diboson excess - Fichet, Sylvain [UNESP]; von Gersdorff, Gero [UNESP] (Springer, 2015)
We classify the complete set of dimension-5 operators relevant for the resonant production of a singlet of spin 0 or 2 linearly coupled to the Standard Model (SM). We compute the decay width of such states as a function of the effective couplings, and provide the matching to various well-motivated New Physics scenarios. We then investigate the possibility that one of these neutral resonances be at the origin of the excess in diboson production recently reported by the ATLAS collaboration. We perform a shape analysis of the excess under full consideration of the systematic uncertainties to extract the width inverted right perpendicular(tot) of the hypothetical resonance, finding it to be in the range 26 GeV < inverted right perpendicular(tot) < 144 GeV at 95% C.L. We then point out that the three overlapping selections W W , W Z, ZZ reported by ATLAS follow a joint trivariate Poisson distribution, which opens the possibility of a thorough likelihood analysis of the event rates. The background systematic uncertainties are also included in our analysis. We show that the data do not require WZ production and could thus in principle be explained by neutral resonances. We then use both the information on the width and the cross section, which prove to be highly complementary, to test the effective Lagrangians of singlet resonances. Regarding specific models, we find that neither scalars coupled via the Higgs-portal nor the Randall-Sundrum (RS) radion can explain the ATLAS anomaly. The RS graviton with all matter on the infrared (IR) brane can in principle fit the observed excess, while the RS model with matter propagating in the bulk requires the presence of IR brane kinetic terms for the gauge fields.
Keywords: Beyond Standard Model; Field Theories in Higher Dimensions; Effective field theories